2006
DOI: 10.1159/000098055
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Hyperintense Vessel Signals on Fluid-Attenuated Inversion Recovery Sequences in Acute Cerebral Ischemia

Abstract: Background: Fluid-attenuated inversion recovery (FLAIR) sequences may reveal hyperintense vessel signals (HVS) at the acute stage of cerebral ischemia. The aim of this study was to test the hypothesis that HVS are associated with a worse outcome. Methods: We included 30 consecutive patients admitted within 12 h after onset of hemispheric cerebral ischemia. The outcome was assessed with the modified Rankin Scale at month 1. Results: Proximal HVS were present in 9 patients and distal HVS in 16. All patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
0
39
0
1
Order By: Relevance
“…4,8 It has been suggested as an indicator of both collateral blood flow and bad outcome after 1 month. 5,9 FHA may be testimony for impaired hemodynamics and insufficient collaterals. 3 Conflicting findings from previous studies may be partly attributable to differing methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 It has been suggested as an indicator of both collateral blood flow and bad outcome after 1 month. 5,9 FHA may be testimony for impaired hemodynamics and insufficient collaterals. 3 Conflicting findings from previous studies may be partly attributable to differing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…They have been interpreted as an indicator of slow blood flow, inadequate collateral circulation, and poor outcome. [3][4][5] Others found no independent association of hyperintense vessels with clinical outcomes. 6 The ischemic cascade is an intricate process involving complex hemodynamics and a series of biochemical reactions on a cellular level.…”
mentioning
confidence: 99%
“…Willis have failed, the presence of secondary collateral pathways is possibly considered a marker for impaired cerebral hemodynamics. 16,17 Furthermore, an ivy sign on FLAIR can be observed in patients with chronic vascular diseases. Two recent studies, 1 of which includes the study reported by our group, revealed that the existence of an ivy sign on a FLAIR image in patients with Moyamoya disease is associated with decreased cerebral VR and development of leptomeningeal collaterals.…”
Section: Figmentioning
confidence: 99%
“…1 Several studies suggest FHV to be indicative of hemodynamic stress, inadequate collateralization, and poor functional recovery. [2][3][4][5] Conversely, others attributed FHV to increased leptomeningeal collateralization and found an association with smaller lesions, slower infarct progression, and better prognosis. [6][7][8][9][10] The apparent contradiction of these studies may stem from the use of different methodologies and the diversity of populations studied, making the plethora of results challenging to analyze.…”
mentioning
confidence: 99%